2005
DOI: 10.1016/j.otohns.2004.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Cooperative Outcomes Group for ENT: A multicenter prospective cohort study on the outcomes of tympanostomy tubes for children with otitis media

Abstract: C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 15 publications
6
24
2
1
Order By: Relevance
“…This is in concordance with other studies reporting on the responsiveness of the OM-6 [5,9-11]. Three studies [5,9,10] present standardized response means (SRM) above 1.0 and conclude that OM-6 is responsive to change [27,37]. The last study [11] concluded that OM-6 was responsive to change using Guyatt’s Responsiveness statistic (GRS) and statistical significance of differences between scores at the different time points.…”
Section: Discussionsupporting
confidence: 92%
“…This is in concordance with other studies reporting on the responsiveness of the OM-6 [5,9-11]. Three studies [5,9,10] present standardized response means (SRM) above 1.0 and conclude that OM-6 is responsive to change [27,37]. The last study [11] concluded that OM-6 was responsive to change using Guyatt’s Responsiveness statistic (GRS) and statistical significance of differences between scores at the different time points.…”
Section: Discussionsupporting
confidence: 92%
“…This may reflect cultural differences in the perception of health and disease, differences in proportions of disease, differences in the severity of disease in populations studied, differences in antibiotic utilisation and/or differences in treatment protocols [8,9]. Therefore, we chose the OM-6 survey as it is simple and easy to use, it has been validated, and it is reliable and sensitive to change [3,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…A number of papers have specifically examined the impact of this procedure on quality of life (QOL), and have consistently reported the benefits of myringotomy with VT insertion [3][4][5][6][7]. There are a multitude of surveys that assessed effect of grommets on quality of life but are difficult to compare the various quality of life instruments used by different researchers.…”
Section: Introductionmentioning
confidence: 99%
“…208 One multicenter, nonrandomized observational study showed large improvements in a disease-specific quality-of-life instrument that measured psychosocial domains of physical suffering, hearing loss, speech impairment, emotional distress, activity limitations, and caregiver concerns that are associated with ear infections. 209 These benefits of tympanostomy tubes have been demonstrated in mixed populations of children that include children with OME as well as recurrent AOM.…”
Section: Surgery For Recurrent Aommentioning
confidence: 99%